Pengaruh Agama dalam Kehidupan Masyarakat TKI Dusun Beji, ‎Ponorogo - Muttaqin Muttaqin; Ali Mahfuz Munawar; Rif’at Husnul Ma’afi (Universitas Darussalam Gontor, 2021)
Becoming an Indonesian migrant worker (TKI) is one option in finding work. The offer to become a migrant worker is even more tempting when you see a neighbor who is successful and able to meet the family's needs. This is also the reason and motivation for the majority of TKI from Beji Hamlet, Polorejo, Babadan District, Ponorogo Regency to become TKI. In Beji, you can find houses with modern styles as a symbol of the success of residents who were former migrant workers. This article will describe the influence of religion on the lives of Indonesian migrant workers from Beji. The research was conducted by extracting information from 13 informants, of which 3 informants were residents who had not become migrant workers, while 10 informants were residents who had previously been migrant workers. To present the data, it is done using the descriptive analysis method. The results were found, TKI from Beji has existed since the 80s with the destination country of Saudi Arabia. Currently, the number of their destination countries includes; Qatar, Saudi Arabia, Korea, Taiwan, Malaysia, and Kuwait. The analysis shows that religion have a big influence on the lives of TKI in Beji Hamlet. The role of religion can be seen in how the TKI from Beji makes a living, educates their children, relates to fellow humans, and is grateful for the benefits they get